A Study on Impact of Foreign Trade In GDP of Nepal - Parajuli, Rita (Interdisciplinary Journal of Management and Social Sciences, 2021)
Foreign trade is a major source of economic revenue for any nation. This study investigates the linkage between economic growth with import and export. The objectives of study are to study the growth trend of foreign trade and to examine the relationship between exports, imports and economy growth of Nepal. The ARDL model has been used to examine the relationship between foreign trade and economic growth of Nepal. The analysis is based on data for the period of 1994/95 to 2018/19. The empirical evidence indicates that there is a stable long run relation of economic growth with foreign trade.